2021
DOI: 10.1177/12034754211027509
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Identifying Culprit Drugs in Cutaneous Drug Eruptions: A Scoping Review

Abstract: Background Cutaneous drug eruptions are a significant source of morbidity, mortality, and cost to the healthcare system. Identifying the culprit drug is essential; however, despite numerous methods being published, there are no consensus guidelines. Objectives Conduct a scoping review to identify all published methods of culprit drug identification for cutaneous drug eruptions, compare the methods, and generate hypotheses for future causality assessment studies. Eligibility criteria Peer-reviewed publications … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…However, identifying a culprit drug from several candidate drugs remains challenging to this date due to multiple candidate drugs, time‐constraints, and sometimes diagnostic urgency 6–8 . A previous study demonstrated that 31% of healthcare practitioners reported, “It is often too difficult to identify the causative drug.” 7 Although several conventional methods (e.g., Naranjo, Jones, and Karch‐Lasagna algorithm) have been used for the identification of the culprit drugs in ADRs, 9–11 these methods did not show acceptable accuracy in medical practice (accuracy 45%) 12 .…”
mentioning
confidence: 99%
“…However, identifying a culprit drug from several candidate drugs remains challenging to this date due to multiple candidate drugs, time‐constraints, and sometimes diagnostic urgency 6–8 . A previous study demonstrated that 31% of healthcare practitioners reported, “It is often too difficult to identify the causative drug.” 7 Although several conventional methods (e.g., Naranjo, Jones, and Karch‐Lasagna algorithm) have been used for the identification of the culprit drugs in ADRs, 9–11 these methods did not show acceptable accuracy in medical practice (accuracy 45%) 12 .…”
mentioning
confidence: 99%